The Effectiveness of Acceptance and Commitment Therapy (ACT) for Reducing Depression in Post-Stroke Patients - Nurmalita Sari; Margaretha Sih Setija Utami; Esthy Rahayu (Faculty of Psychology, Universitas Semarang, 2022)
Abstract. Stroke will experience setbacks such as difficulty in thinking, speaking and moving. This condition creates a feeling of helplessness with his life, so that post-stroke patients are prone to depression. The purpose of this study was to determine the effect of giving Acceptance and Commitment Therapy (ACT) in reducing depression in post-stroke patients. This study involved 6 post-stroke participants with major depression. The research method used was quantitative- true eksperiment. Based on the results of the Mann-Whitney posttest, there was a significant difference in scores between the groups that were given Acceptance and Commitment Therapy (ACT) and those who were not given Acceptance and Commitment Therapy (ACT) (0.023; p <0.05). So it can be concluded that Acceptance and Commitment Therapy (ACT) can be used to reduce depression in post-stroke patients.Keywords: Depression, Acceptance and Commitment Therapy (ACT), post-stroke.Abstrak. Stroke akan menyebabkan seseorang mengalami kemunduran seperti kesulitan dalam berpikir, berbicara dan bergerak. Kondisi ini menimbulkan perasaan tidak berdaya dengan hidupnya, sehingga pasien pasca-stroke rentan terhadap depresi. Tujuan penelitian ini adalah untuk menguji pengaruh Acceptance and Commitment Therapy (ACT) dalam menurunkan depresi pada pasien pasca-stroke. Penelitian ini melibatkan 6 partisipan pasca-stroke dengan depresi berat. Metode penelitian yang digunakan adalah kuantitatif-true eksperimen. Berdasarkan hasil posttest uji Mann-Whitney menunjukkan adanya perbedaan skor depresi yang signifikan antara kelompok yang diberikan Acceptance and Commitment Therapy (ACT) dan kelompok yang tidak diberikan Acceptance and Commitment Therapy (ACT) (0,023; p<0,05). Maka dapat disimpulkan bahwa Acceptance and Commitment Therapy (ACT) efektif digunakan untuk menurunkan depresi pada pasien pasca-stroke.Kata kunci: Depresi, Acceptance and Commitment Therapy (ACT), pasca-stroke.